2019
DOI: 10.1016/j.aim.2019.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Optimal bounds for T-singularities in stable surfaces

Abstract: We explicitly bound T-singularities on normal projective surfaces W with one singularity, and KW ample. This bound depends only on K 2 W , and it is optimal when W is not rational. We classify and realize surfaces attaining the bound for each Kodaira dimension of the minimal resolution of W . This answers effectiveness of bounds (see [A94], [AM04], [L99]) for those surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 21 publications
1
39
0
Order By: Relevance
“…Since the closure of the locus of smooth I-surfaces is irreducible of dimension 28, we conclude that the general surface obtained via this construction is not smoothable. This confirms the infinitesimal computations of [23], where it is shown that the obstruction space for Q-Gorenstein deformations is non-zero for these surfaces.…”
Section: Remark 317supporting
confidence: 87%
See 2 more Smart Citations
“…Since the closure of the locus of smooth I-surfaces is irreducible of dimension 28, we conclude that the general surface obtained via this construction is not smoothable. This confirms the infinitesimal computations of [23], where it is shown that the obstruction space for Q-Gorenstein deformations is non-zero for these surfaces.…”
Section: Remark 317supporting
confidence: 87%
“…As explained in the introduction of [23], the log Bomolov-Miyaoka-Yau inequality gives d ≤ 34 for a stable I-surface with a T-singularity of type 1 4d (1, 2d − 1), a weaker bound than Proposition 3.4 (i).…”
Section: Remark 35mentioning
confidence: 96%
See 1 more Smart Citation
“…After the first version of this paper was prepared, in June 2017, we learned that a very similar (slightly stronger, and optimal) result had been proved by Rana and Urzúa[RU19]. They use algebro-geometric rather than symplectic methods, so do not recover our purely symplectic Theorem 1.4.…”
mentioning
confidence: 88%
“…The authors would like to thank Weiyi Zhang for extremely helpful discussions about how −1spheres can degenerate under Gromov compactness (see Remark 2.14) and how our paper might generalise beyond the p g > 0 setting, Paul Hacking for useful comments and for making us aware of the ongoing work of Rana and Urzúa, Julie Rana, and Giancarlo Urzúa for constructive discussions once we learned about their work [RU19], and the anonymous referee for their comments.…”
Section: Acknowledgementsmentioning
confidence: 99%